Influence of growth rings position of wood on the determination of its shear strength parallel to grain - Rodrigues, E. F. C.; De Araujo, V. A. [UNESP]; Cavalheiro, R. S.; Marini, L. J.; Almeida, J. P. B.; Azevedo, A. R. G.; Oliveira, L. B.; Lahr, F. A. R.; Santos, H. F. dos; Christoforo, A. L. (Elsevier B.V., 2023)
This study aimed to determine the longitudinal-radial (LR) and longitudinal-tangential (LT) shear strength properties (fvLR, and fvLT) for three wood species (Hymenolobium petraeum, Erisma uncinatum and Couratari sp) as a way to correlate the strength between planes through the evaluation by analysis of variance and validation tests. Shear strength, compressive strength and anatomical characterization tests were carried out to support the evaluation of correlations. The results revealed that the shear strength was statistically different (p-value <0.05) when the load plane was changed for all three species. Hymeno-lobium petraeum (fvLT = 6.36 MPa; fvLR = 12.68 MPa) and Couratari sp (fvLT = 11.73 MPa; fvLR = 12.97 MPa) species were stronger in the LR plane than in the LT plane, while E. uncinatum wood was weaker in the LR plane (fvLT = 13.81 MPa; fvLR = 9, 97 MPa). In addition, H. petraeum showed the greatest difference between the characteristic results when two planes were compared each other. Therefore, these species should be always tested in their weakest plane, in order to prevent the undersized design of their cross sections. The cor-relation between anatomical characteristics and shear strength demonstrated that the width and frequency of rays, axial parenchyma, grouping of vessels and fibrous zones are strong factors that influenced the shear results. Moreover, the correlation between char-acteristic values of shear strength and compressive strength prescribed by the Brazilian standard code proved to be conservative for hardwoods.& COPY; 2023 Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Shear strength; Longitudinal-tangential plane; Longitudinal-radial plane; Ratio between shear and; compression strength; Photomicrograph; Anatomical features; Brazilian hardwoods